Numerical and Experimental Analysis of the Anisotropy Evolution in Aluminium Alloys Processed by Asymmetric Rolling - Vincze, Gabriela; Lopes, Augusto; Butuc, Marilena C.; Yánez, Jesús; Lopes, Diogo; Holz, Laura; Graça, Ana; Pereira, António B. (European Journal of Computational Mechanics, 2022)
One of the most important characteristics of the sheet metal is its anisotropy. Asymmetric rolling (ASR) shows to be an adequate process to change the material anisotropy by increasing the normal anisotropy and decreasing the planar anisotropy. In this work, it is analysed the relationship between anisotropy and texture evolution using experimental and numerical approaches. Experimentally, the texture is modified by rolling, involving symmetric (SR), asymmetric rolling continuous (ARC) and asymmetric reverse (ARR) routes and different reductions per pass. The numerical analysis was performed through the visco-plastic self-consistent model where two hardening laws were considered, namely the Voce-type (V) and the dislocation density-based model (DDR). The main objective of the numerical method was to test the performance of the VPSC model for large plastic deformation. The Lankford coefficients decrease in RD and increase in TD with the increase in the total thickness reduction. This trend observed experimentally is well captured by the VPSC model, however, in terms of R-value, an overestimation is observed in both cases with better results for Voce-type law.